Cooperation of immune regulators Tollip and surfactant protein A inhibits influenza A virus infection in mice - Niccolette Schaunaman; Diana Cervantes; Taylor Nichols; Mari Numata; Julie G. Ledford; Monica Kraft; Hong Wei Chu (Respiratory Research, 2024)
Abstract Background Influenza A virus (IAV) infection is a significant risk factor for respiratory diseases, but the host defense mechanisms against IAV remain to be defined. Immune regulators such as surfactant protein A (SP-A) and Toll-interacting protein (Tollip) have been shown to be involved in IAV infection, but whether SP-A and Tollip cooperate in more effective host defense against IAV infection has not been investigated. Methods Wild-type (WT), Tollip knockout (KO), SP-A KO, and Tollip/SP-A double KO (dKO) mice were infected with IAV for four days. Lung macrophages were isolated for bulk RNA sequencing. Precision-cut lung slices (PCLS) from WT and dKO mice were pre-treated with SP-A and then infected with IAV for 48 h. Results Viral load was significantly increased in bronchoalveolar lavage (BAL) fluid of dKO mice compared to all other strains of mice. dKO mice had significantly less recruitment of neutrophils into the lung compared to Tollip KO mice. SP-A treatment of PCLS enhanced expression of TNF and reduced viral load in dKO mouse lung tissue. Pathway analysis of bulk RNA sequencing data suggests that macrophages from IAV-infected dKO mice reduced expression of genes involved in neutrophil recruitment, IL-17 signaling, and Toll-like receptor signaling. Conclusions Our data suggests that both Tollip and SP-A are essential for the lung to exert more effective innate defense against IAV infection.